Age Weakens the Other-Race Effect among Han Subjects in Recognizing Own- and Other-Ethnicity Faces - Jialin Ma; Rui Zhang; Yongxin Li (Behavioral Sciences, 2023)
The development and change in the other-race effect (ORE) in different age groups have always been a focus of researchers. Previous studies have mainly focused on the influence of maturity of life (from infancy to early adulthood) on the ORE, while few researchers have explored the ORE in older people. Therefore, this study used behavioral and eye movement techniques to explore the influence of age on the ORE and the visual scanning pattern of Han subjects recognizing own- and other-ethnicity faces. All participants were asked to complete a study-recognition task for faces, and the behavioral results showed that the ORE of elderly Han subjects was significantly lower than that of young Han subjects. The results of eye movement showed that there were significant differences in the visual scanning pattern of young subjects in recognizing the faces of individuals of their own ethnicity and other ethnicities, which were mainly reflected in the differences in looking at the nose and mouth, while the differences were reduced in the elderly subjects. The elderly subjects used similar scanning patterns to recognize the own- and other-ethnicity faces. This indicates that as age increases, the ORE of older people in recognizing faces of those from different ethnic groups becomes weaker, and elderly subjects have more similar visual scanning patterns in recognizing faces of their own and other ethnicities.